Occurrence of polycyclic aromatic hydrocarbons, microplastics and biofilms in Alqueva surface water at touristic spots - Raposo, Ana (2022)
Freshwater pollution is a huge concern. A study aiming to evaluate physico-chemical characteristics, microbiota, occurrence of two groups of persistent environmental pollutants with similar chemical properties (polycyclic aromatic hydrocarbons- PAHs and microplastics - MPs) in Alqueva's surface water was performed during 2021. Water samples were collected at three spots related to touristic activities (two beaches and one marina) during the Winter, Spring, Summer and Autumn seasons. In addition, the presence of biofilms on plastic and natural materials (stone, wood/ vegetal materials) were assessed and compared. Water quality based on physicochemical parameters was acceptable with a low eutrophication level. PAHs concentration levels were lower than the standard limits established for surface waters by international organizations. However, carcinogenic compounds were detected in two sampling locations, which can pose a problem for aquatic ecosystems. PAHs profiles showed significant differences when comparing the dry seasons with the rainy seasons, with a higher number of different compounds detected in Spring. Low molecular weigh compounds, usually associated with the atmospheric deposition and petroleum contamination, were more prevalent. MPs were detected in all samples except one during the Winter season. The polymers detected were poly(methyl-2-methylpropenoate), polystyrene, polyethylene terephthalate, polyamide, polypropylene, styrene butadiene, polyvinyl chloride and low /high density polyethylene with the last being the most frequent. Biofilms were more often detected on plastics than on natural materials. In addition, biofilms detected on plastics were more complex with higher microbial diversity (e.g., bacteria, fungi/yeast and phytoplancton organisms) and richer in extrapolymeric material. Based on morphological analysis a good agreement between microbiota and microorganism present in the biofilms was found. Among microbiota were identified microorganisms previously linked to plastic and PAHs detoxification suggesting the need for further studies to evaluate the viability of using biofilms as part of a green bioremediation strategy to mitigate water pollution.